Positioning Citra PKS di Mata Konstituen (Sebuah Pendekatan Brand Association Terhadap Konstituen PKS di Kelurahan Jati, Kecamatan Pulogadung, Jakarta Timur ) - Angelika Rosma (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
This research analyzes the Positioning of PKS image to its constituents in Jati Village, Pulogadung Sub-district. The positioning of this party image uses the theory of brand association and positioning theory. This research uses quantitative approach with survey method and cluster analysis. The largest cluster result shows that PKS image is still good and its positioning is the Da'wah Party.